Gradient composite coating for copper-based part and method for applying gradient composite coating to additive repair
By forming a nickel-based alloy transition layer and a copper-based alloy surface layer on the surface of the copper-based part and performing anodization treatment, the problems of low laser energy absorption and poor corrosion resistance of the coating during the surface cladding of the copper-based part are solved, and the problem of low laser energy absorption and poor coating corrosion resistance is achieved. The improvement of mechanical properties and crack prevention significantly improve the strength and comprehensive mechanical properties of the metallurgical coating.
Patent Information
- Application Number
- CN202411092086.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The direct cladding of copper-based parts has problems such as low laser energy absorption, poor corrosion resistance of the coating, and prone to crack defects.
A gradient composite coating with a two-layer structure includes a nickel-based alloy transition layer and a copper-based alloy surface layer, and anodized on the surface of the nickel-based alloy transition layer to form an anodized layer, optimize the interaction between laser and metal, and improve the Mechanical properties of copper alloy cladding.
The stress ratio balance between the matrix part and the cladding layer is achieved, crack defects are avoided, and the strength and comprehensive mechanical properties of the metallurgical coating are improved. The tensile strength reaches 399MPa and the maximum yield strength reaches 319MPa.
Smart Images

Figure CN119121225A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite laser additive engineering, in particular to a gradient composite coating for the surface of a copper-based part and a method for applying the coating to additive repair. Background Art
[0002] In the prior art, copper and copper alloys have excellent seawater corrosion resistance and marine biological corrosion resistance, and are widely used in key parts of marine engineering. However, due to their low strength and poor wear resistance, the surface of parts often fails due to wear, cavitation, etc., thus affecting the service performance and service life of copper alloy parts. Therefore, repairing the failure surface of copper-based parts is of great significance for extending the service life of copper-based parts and reducing resource waste.
[0003] However, there are special difficulties in directly cladding copper alloys on the surface of copper-based parts. Since copper has a high infrared laser reflectivity, the laser energy absorption rate in the copper composite powder laser cladding process is low, and the cladding process cannot be completed normally. Secondly, the coating prepared by copper composite powder cladding has intergranular corrosion and pinhole corrosion, and the corrosion resistance of the coating is significantly lower than the surface corrosion resistance of the copper-based prototype parts. The mechanical properties of the laser-clad copper alloy layer are lower than those of the original copper-based parts. Direct cladding of copper alloy will lead to stress mismatch between the cladding layer and the substrate, which is prone to fracture defects.
[0004] Therefore, the market urgently needs a method to effectively solve the difficulties of direct cladding of copper alloys, which can effectively prevent the occurrence of defects such as cracks and make the metallurgical coating have excellent strength and comprehensive mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to provide an improved gradient composite coating for copper-based parts and an application method thereof. Through process improvement, the composite coating with a gradient structure can achieve a decrease in mechanical properties, thereby ensuring a stress ratio balance between the base part and the surface cladding layer, effectively preventing the occurrence of defects such as cracks, and making the metallurgical coating have excellent strength and comprehensive mechanical properties.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the present invention is: a gradient composite coating for copper-based parts, characterized in that: the gradient composite coating is a double-layer structure, including a nickel-based alloy transition layer and a copper-based alloy surface layer, and an anodized layer is provided between the nickel-based alloy transition layer and the copper-based alloy surface layer; the surface of the nickel-based alloy transition layer is roughened by an anodizing method to form an anodized layer.
[0007] A method for additive repair using a gradient composite coating on the surface of a copper-based part, characterized in that the additive repair method comprises the following steps: a. pre-treating the surface of the copper-based part to remove the fatigue layer and the damage layer on the surface so that the bottom of the defect of the copper alloy part is completely exposed; b. preparing a nickel-based alloy coating on the surface of the copper-based part to form a nickel-based alloy transition layer; c. anodizing the surface of the laser additive nickel-based coating to increase the surface roughness of the nickel-based coating; d. laser cladding of a copper-based material on the surface of the anodized nickel-based coating to form a copper-based alloy surface layer; e. after the laser cladding process is completed, finishing the surface by polishing to restore the flatness and complete the surface repair of the copper-based part.
[0008] Preferably, in step a, the surface of the copper-based part is machined to first remove the rust layer and oxide film on the groove surface, then use sandpaper to polish the surface of the part substrate to make it smooth, wipe the surface of the part with alcohol and acetone, and then dry it to remove grease and impurities on the surface.
[0009] Furthermore, in step b, the copper-based parts pretreated in step a are preheated at a temperature of 180-250°C, and then laser cladding of nickel-based alloy is performed on the surface of the copper-based parts to form a nickel-based alloy transition layer.
[0010] Furthermore, in step c, the surface of the nickel-based metallurgical coating is roughened by an electrodeposition-anodization method, a test plate is selected as an electroplating anode, an epoxy resin-titanium alloy cathode is used as an electroplating cathode, and a low-frequency signal generator is used for pulse current electroplating to finally form an anodized layer.
[0011] Furthermore, in step d, the copper-based part is preheated at a temperature of 180-250°C, and then a copper alloy is used as a cladding material on the surface of the anodized layer, and a laser cladding process is used to form a copper-based alloy surface layer on the surface of the copper-based part.
[0012] Furthermore, in step b, a nickel-based corrosion-resistant alloy is selected as the cladding material, and a laser composite cladding process is used to form a nickel-based alloy metallurgical coating, so that no defects are generated in the laser cladding area.
[0013] Compared with the prior art, the technical solution of the present invention not only improves the overall technical solution, but also includes many improvements in details. Specifically, it has the following beneficial effects: The improved solution of the present invention is that the gradient composite coating is a double-layer structure, including a nickel-based alloy transition layer and a copper-based alloy surface layer, and an anodized layer is provided between the nickel-based alloy transition layer and the copper-based alloy surface layer; the surface of the nickel-based alloy transition layer is roughened by an anodizing method to form an anodized layer, which optimizes the interaction between the laser and the metal, improves the metal's absorption rate of the laser, and ensures the excellent performance of the surface copper alloy cladding layer; In the technical solution of the present invention, a nickel-based alloy coating is prepared on the surface of a copper-based part to form a nickel-based alloy transition layer, the surface of the laser additive nickel-based coating is anodized to increase the surface roughness of the nickel-based coating, and a copper-based material is laser clad on the surface of the anodized nickel-based coating to form a copper-based alloy surface layer; the composite coating with a gradient structure formed in this way can achieve a decrease in mechanical properties, thereby ensuring a balanced stress ratio between the base part and the surface cladding layer, effectively preventing the generation of defects such as cracks, and making the metallurgical coating have better strength and comprehensive mechanical properties; In the technical solution of the present invention, a multi-layer additive structure is used to repair copper-based parts, and nickel-based alloy-copper alloy cladding is performed in sequence, which can effectively avoid the problems existing in direct cladding of copper alloy, so that the laser additive area has a gradient decreasing trend of mechanical properties, avoiding the generation of problems such as poor bonding, poor stress matching, and crack defects; The additive repair method for copper-based parts of the present invention has a simple process and is easy to implement. The gradient composite coating formed has a tensile strength of 399 MPa and a maximum yield strength of 319 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a structural schematic diagram of the present invention.
[0015] Figure 2 This is a microscopic photograph of the surface after an anodic oxide layer is formed on the nickel-based alloy transition layer of the present invention.
[0016] Figure 3 The figure is a schematic diagram of a stress-strain curve formed by a uniaxial tensile test of the gradient composite coating of the present invention.
[0017] Reference numerals: 1. Copper-based parts, 2. Nickel-based alloy transition layer, 3. Copper-based alloy surface layer, 4. Anodized layer. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention provides a gradient composite coating for copper-based parts, which is different from the prior art in that: the gradient composite coating is a double-layer structure, including a nickel-based alloy transition layer 2 and a copper-based alloy surface layer 3, and an anodized layer 4 is provided between the nickel-based alloy transition layer 2 and the copper-based alloy surface layer 3; the surface of the nickel-based alloy transition layer is roughened by an anodizing method to form an anodized layer.
[0020] When in use, the present invention adopts a multi-layer additive structure to repair copper-based parts, which can effectively avoid the problems existing in direct cladding of copper alloys, and sequentially clads nickel-based alloys and copper alloys, so that the laser additive area has a gradient decreasing trend in mechanical properties, effectively avoiding the occurrence of problems such as poor bonding, poor stress matching, and crack defects. At the same time, the surface of the nickel-based alloy additive is anodized to increase the roughness of the metal surface, optimize the interaction between the laser and the metal, increase the metal's absorption rate of the laser, and improve the cladding performance of the surface copper alloy cladding layer. Example 1
[0021] In this embodiment, the present invention provides a method for applying a gradient composite coating on the surface of a copper-based part to additive repair, comprising the following steps: a. pretreating the surface of the copper-based part to remove the fatigue layer and the damage layer on the surface so that the bottom of the defect of the copper alloy part is completely exposed; b. preparing a nickel-based alloy coating on the surface of the copper-based part to form a nickel-based alloy transition layer; c. anodizing the surface of the laser additive nickel-based coating to increase the surface roughness of the nickel-based coating; d. laser cladding a copper-based material on the surface of the anodized nickel-based coating to form a copper-based alloy surface layer; e. after the laser cladding process is completed, finishing the surface by polishing to restore the flatness and complete the surface repair of the copper-based part.
[0022] Specifically, the surface of the copper-based parts is first polished to remove the fatigue layer and the damage layer, so that the bottom of the defects of the copper alloy parts are completely exposed, and the oxides around the defects are removed. Then, the defects and surrounding surfaces are cleaned with a cleaning agent to remove oil and dust.
[0023] Then, a nickel-based alloy coating is prepared on the surface of the copper-based parts. As a commonly used laser cladding material, nickel-based alloy has good cladding performance, no defects are generated during the laser additive process, and its strength, hardness and other indicators are similar to those of the substrate, and it has strong comprehensive mechanical properties.
[0024] Secondly, the surface of the laser additive nickel-based coating is anodized to increase the surface roughness of the nickel-based coating.
[0025] Finally, laser cladding of copper-based materials is performed on the surface of the anodized nickel-based coating, and the same material as the original copper-based parts is selected as the cladding material. After the laser cladding process is completed, the surface is finished by polishing to restore the flatness.
[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. The use of a multi-layer additive structure to repair copper-based parts and sequentially cladding of nickel-based alloy-copper alloy can effectively avoid the problems existing in direct cladding of copper alloy, so that the laser additive area has a gradient decreasing trend of mechanical properties, avoiding the occurrence of problems such as poor bonding, poor stress matching, and crack defects.
[0027] 2. Perform anodizing treatment on the surface of nickel-based alloy additives to improve the roughness of the metal surface, optimize the interaction between laser and metal, increase the metal's absorption rate of laser, and improve the cladding performance of the surface copper alloy cladding layer. Multi-layer additive structure.
[0028] 3. The coating preparation process uses laser-CMT composite cladding process with small heat input to avoid the impact of excessive heat input on the body. At the same time, metallurgical bonding makes the coating and the substrate have a strong bonding force. Example 2
[0029] In this embodiment, the present invention provides a method for applying a gradient composite coating on the surface of a copper-based part to additive repair, comprising the following steps: a. pretreating the surface of the copper-based part to remove the fatigue layer and the damage layer on the surface so that the bottom of the defect of the copper alloy part is completely exposed; b. preparing a nickel-based alloy coating on the surface of the copper-based part to form a nickel-based alloy transition layer; c. anodizing the surface of the laser additive nickel-based coating to increase the surface roughness of the nickel-based coating; d. laser cladding of a copper-based material on the surface of the anodized nickel-based coating to form a copper-based alloy surface layer; e. after the laser cladding process is completed, finishing the surface by polishing to restore the flatness and complete the surface repair of the copper-based part.
[0030] Specifically, in step a, the surface of the copper-based part is machined to first remove the rust layer and oxide film on the groove surface, then use sandpaper to polish the surface of the part base to make it smooth, wipe the surface of the part with alcohol and acetone, and then dry it to remove grease and impurities on the surface.
[0031] In step b, the copper-based part pretreated in step a is preheated at a temperature of 180-250° C., and then a nickel-based alloy is laser clad on the surface of the copper-based part to form a nickel-based alloy transition layer. Furthermore, a nickel-based corrosion-resistant alloy is selected as the cladding material, and a nickel-based alloy metallurgical coating is formed by a laser composite cladding process, so that no defects are generated in the laser cladding area.
[0032] In step c, the surface of the nickel-based metallurgical coating is roughened by electroplating-anodizing, and a test plate with a nickel-based metallurgical coating melted on the surface is selected as an electroplating anode. The electroplating cathode uses an epoxy resin-titanium alloy cathode. During the preparation of the epoxy resin-titanium alloy cathode, the copper wire is first bonded to one side of the titanium alloy plate with a conductive adhesive, and the titanium alloy plate is placed in an environment of 200°C and heated for 2-3 hours. After cooling, the side bonded with the copper wire is coated with epoxy resin to complete the preparation of the cathode. A low-frequency signal generator is used for pulse current electroplating to finally form an anodic oxide layer. Further, the electroplating solution here is 30g / l of boric acid and 200g / l of nickel sulfate, and a signal generator with a pulse frequency of 200Hz is used for pulse current electroplating. The concentration of the electrochemical oxidizing medium KOH is 4mol / l, the oxidation temperature is 60°C, and the voltage is 1.1V.
[0033] The mass percentages of the components of the electroplating solution are 70% water solvent, 20% nickel sulfate, 3% boric acid, 6% acetone and 1% potassium hydroxide.
[0034] In step d, the copper-based parts are preheated at a temperature of 180-250°C, and then on the surface of the anodized layer, a copper alloy is used as a cladding material, and a copper-based alloy surface layer is formed on the surface of the copper-based parts by a laser cladding process, and the thickness of the nickel-based alloy metallurgical coating is 3-4 mm. Further, a copper alloy of the same material as the copper-based parts is selected as a cladding material, and a copper-based alloy surface layer is formed by a laser composite cladding process, so that no defects are generated in the laser cladding area, and a gradient composite coating is formed, and the tensile strength of the gradient composite coating reaches 399 MPa, and the maximum yield strength reaches 319 MPa. Example 3
[0035] In this embodiment, the gradient composite coating is a double-layer structure (see Figure 1 ), including a nickel-based alloy transition layer and a copper-based alloy surface layer, an anodized layer is provided between the nickel-based alloy transition layer and the copper-based alloy surface layer; the surface of the nickel-based alloy transition layer is roughened by an anodizing method to form an anodized layer.
[0036] The method for applying the gradient composite coating on the surface of copper-based parts to additive repair includes the following steps: first, mechanically process the substrate surface of the copper-based parts to remove the rust layer and oxide film on the groove surface to prevent pores and cracks from being generated during the laser cladding process; use sandpaper to polish the substrate surface smoothly, wipe the surface with alcohol and acetone and dry it to remove grease and impurities on the surface; then preheat the substrate of the parts, and after reaching a certain preheating temperature, laser clad the nickel-based alloy to prepare the coating; select C267 nickel-based corrosion-resistant alloy as the cladding material, and use laser composite cladding process to form a nickel-based alloy metallurgical coating. Then, the surface of the nickel-based metallurgical coating is roughened by electrodeposition-anodization, the test plate is selected as the electroplating anode, the electroplating cathode uses a homemade epoxy resin-titanium alloy cathode, and a low-frequency signal generator is used for pulse current electroplating. Finally, the anodized plate is preheated, and after reaching a certain preheating temperature, the copper alloy is laser clad to prepare a coating; a copper alloy of the same material as the copper-based parts is selected as the cladding material, and a laser cladding process is used to form a copper alloy metallurgical layer.
[0037] like Figure 1 As shown, the gradient composite coating is a double-layer structure, including a nickel-based alloy transition layer and a copper-based alloy surface layer, and an anodized layer is provided between the nickel-based alloy transition layer and the copper-based alloy surface layer. Figure 1 The multilayer structure shown is used to prepare the surface gradient of the copper-based parts in accordance with the metallurgical coating. The damaged parts on the surface of the copper-based parts are cleaned by polishing to remove the damaged layer and the fatigue layer. The surface roughness after polishing is maintained in the range of Ra6.3~Ra12.5. The copper-based part substrate is preheated to 200°C and then laser cladding of the nickel-based alloy is performed. The laser cladding process parameters are: current of 120A, laser power of 2000W, defocus of +2mm, wire distance of 2mm, additive speed of 10mm / sec, and shielding gas flow rate of 15L / min. The nickel-based alloy cladding performance is good, and no defects are generated in the laser cladding area.
[0038] The surface of the nickel-based coating after cladding was anodized. The electroplating solution was 30g / l boric acid and 200g / l nickel sulfate, the pulse frequency was 200Hz, the electrochemical oxidation medium KOH concentration was 4mol / l, the oxidation temperature was 60℃, and the voltage was 1.1V. The surface microstructure is as follows: Figure 2As shown. After the oxidation of the nickel-based metallurgical coating surface prototype was completed, the surface copper alloy metallurgical coating was prepared, the plate was preheated to 200°C, and the laser cladding process parameters were: current of 100A, laser power of 1500W, defocus of +2mm, wire distance of 2mm, additive speed of 12mm / sec, and protective gas flow of 15L / min. The formed surface copper alloy metallurgical coating was well fused, and no defects were generated in the laser cladding area. The prepared gradient metallurgical coating was subjected to a uniaxial tensile test, and the stress-strain curve was shown in Figure 3 As shown, the tensile strength of the metallurgical coating is 399.627 MPa. According to the plastic elongation of 0.2% nominal yield strength instead of the yield strength value of the alloy, the maximum yield strength is 319.702 MPa.
[0039] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to the above descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. Gradient composite coating for copper-based parts, characterized by: The gradient composite coating is a double-layer structure, including a nickel-based alloy transition layer and a copper-based alloy surface layer, an anodized layer is arranged between the nickel-based alloy transition layer and the copper-based alloy surface layer; the surface of the nickel-based alloy transition layer is roughened by an anodizing method to form an anodized layer.
2. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 1 is characterized in that: The additive repair method includes the following steps: a. pre-treating the surface of the copper-based part to remove the fatigue layer and the damage layer on the surface so that the bottom of the defect of the copper alloy part is completely exposed; b. preparing a nickel-based alloy coating on the surface of the copper-based part to form a nickel-based alloy transition layer; c. Anodize the surface of the laser additive nickel-based coating to increase the surface roughness of the nickel-based coating; d. Laser cladding of copper-based materials is performed on the surface of the anodized nickel-based coating to form a copper-based alloy surface layer; e. After the laser cladding process is completed, the surface is finely processed by polishing to restore the flatness and complete the surface repair of the copper-based parts.
3. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 2, characterized in that: In step a, the surface of the copper-based part is machined to remove the rust layer and oxide film on the groove surface, then the surface of the part base is polished smooth with sandpaper, and the surface of the part is wiped with alcohol and acetone, and then dried to remove grease and impurities on the surface.
4. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 2, characterized in that: In step b, the copper-based parts pretreated in step a are preheated at a temperature of 180-250° C., and then laser cladding of nickel-based alloy is performed on the surface of the copper-based parts to form a nickel-based alloy transition layer.
5. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 2, characterized in that: In step c, the surface of the nickel-based metallurgical coating is roughened by electrodeposition-anodization, a test plate with a nickel-based metallurgical coating melted on the surface is selected as an electroplating anode, an epoxy resin-titanium alloy cathode is used as an electroplating cathode, and a low-frequency signal generator is used for pulse current electroplating to finally form an anodic oxide layer.
6. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 5, characterized in that: During the preparation of the epoxy resin-titanium alloy cathode, the copper wire is first glued to one side of the titanium alloy plate with conductive glue, and the titanium alloy plate is heated at 200°C for 2 to 3 hours. After cooling, the side with the copper wire is coated with epoxy resin to complete the preparation of the cathode.
7. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 2, characterized in that: In step d, the copper-based part is preheated at a temperature of 180-250°C, and then a copper alloy is used as a cladding material on the surface of the anodized layer, and a copper-based alloy surface layer is formed on the surface of the copper-based part by a laser cladding process.
8. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 4, characterized in that: In step b, a nickel-based corrosion-resistant alloy is selected as the cladding material, and a laser composite cladding process is used to form a nickel-based alloy metallurgical coating, so that no defects are generated in the laser cladding area, and the thickness of the nickel-based alloy metallurgical coating is 3~4mm.
9. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 5, characterized in that: In step c, the electroplating solution is 30g / l boric acid and 200g / l nickel sulfate, and a signal generator with a pulse frequency of 200Hz is used for pulse current electroplating. The concentration of electrochemical oxidizing medium KOH is 4mol / l, the oxidation temperature is 60°C, and the voltage is 1.1V.
10. The method for applying the gradient composite coating on the surface of copper-based parts to additive repair according to claim 6, characterized in that: In step d, a copper alloy of the same material as the copper-based parts is selected as the cladding material, and a laser composite cladding process is used to form a surface layer of the copper-based alloy, so that no defects are generated in the laser cladding area, and a gradient composite coating is formed. The tensile strength of the gradient composite coating reaches 399 MPa, and the maximum yield strength reaches 319 MPa.
